Exploitation of linguistic ambiguity in Polish and English jokes - Lew, Robert (Adam Mickiewicz University, 1996)
English & Polish jokes based on linguistic ambiguity are constrasted. Linguistic ambiguity results from a multiplicity of semantic interpretations motivated by structural pattern. The meanings can be "translated" either by variations of the corresponding minimal strings or by specifying the type & extent of modification needed between the two interpretations. C. F. Hockett's (1972) translatability notion that a joke is linguistic if it cannot readily be translated into other languages without losing its humor is used to interpret some cross-linguistic jokes. It is claimed that additional intralinguistic criteria are needed to classify jokes. By using a syntactic representation, the humor can be explained & compared cross-linguistically. Since the mapping of semantic values onto lexical units is highly language specific, translatability is much less frequent with lexical ambiguity. Similarly, phonological jokes are not usually translatable. Pragmatic ambiguity can be translated on the basis of H. P. Grice's (1975) cooperative principle of conversation that calls for discourse interpretations. If the distinction between linguistic & nonlinguistic jokes is based on translatability, pragmatic jokes must be excluded from the classification. Because of their universality, pragmatic jokes should be included into the linguistic classification by going beyond the translatability criteria & using intralinguistic features to describe them.
Keywords: ambiguity; jokes; humour; humor; English; Polish